#### Answer

6

#### Work Step by Step

From the table, we see that: $f(2)=3$ and $g(3)=6$, so we have:
$(g\circ f)(2)=g(f(2))=g(3)=6$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

6

From the table, we see that: $f(2)=3$ and $g(3)=6$, so we have:
$(g\circ f)(2)=g(f(2))=g(3)=6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.